Niveles de actividad física e IMC en estudiantes de 13 a 18 años de la I.E. General Santander e I.E. Jesús Maestro del municipio de Montenegro-Quindío (2019)
This research Project aims at finding the level of physical activity and the body mass index (BMI) of student within the age range of 13 & 18 from General Santander high school and Jesus Maestro high school located in Montenegro, Quindio. Having done this, it was posible to determine the frequency of the physical activity by the appication of the PAQ-A instrument, which is an internationaly established and acepted poll that encompasses questions asked to the particpants of bath institutions taking into accont both genders (masculine- feminine) & the body measurements of weight & size. The latter info was obtained by using a Taylor measure tape and a scale. This descriptive investigation with a quantitative approach was carried out with a total of 390 participants (secundary school stedents) of which 190 were from Jesus Maestro high school and the othe 200 were from General Santander high school; and regardins their genders, there were 192 boys and 198 girls. Currently, studies related to the physical activity in teenagers have reached their peak and shown huge importance due to improve people´s quality of life. To achieve trustworthiness and reliability, this research was based, at some degree, on the astcomes and contributions of investigations of the World Health organization (WHO) regardirg thr causes of physical inactivy, statistics, and benefits that promote strategies development that lead to the inprovement of both health & quality of life.